The Impact of Financial Performance and Company Size on The Disclosure of Sustainability Report - Hibatun Naeem; Ignatius Oki Dewa Brata (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2019)
The trend regarding Sustainability Reporting in Indonesia is experiencing positive developments. Conclusion can be drawn that companies already have an awareness that the company's survival depends on the company's relationship with the environment, this is following the legitimacy theory which states that the company has a contract with the community to carry out its activities based on the values of justice and how the company responds to various interest groups to legitimize company actions. Therefore, in this research, the researchers wanted to examine which of the more effective influences triggers in the development of an upward trend in Sustainability Reporting, from several samples taken by researchers it has been obtained data that represents financial performance and company size, after being processed using logistic regression, obtained data that states that the size of the company is the most powerful influence in disclosing the sustainability report.